PENGARUH PUPUK KOMPOS, MIKORIZA ARBUSKULAR, DAN BIOSAKA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG PADA TANAH SALIN - D, Rahmad; Syamsoraya, Dwi Ramadani; Nurhalisyah, Nurhalisyah (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2025)
Corn (Zea mays L.) is one of the important food commodities in Indonesia. The use of corn, especially as an industrial raw material and animal feed, continues to increase. Increasing corn production can be done by utilizing sub-optimal soils, one of which is saline soil. The purpose of this study is to determine the effect of compost fertilizer, arbuscular mycorrhizae and biosaka on the production of corn plants in saline soil. The research consisted of 5 treatments, namely; chemical fertilizers., compost fertilizers., Compost fertilizers and arbuscular Mycorrhiza., Compost and Biosaka., Compost fertilizers, arbuscular mycorrhiza, and Biosaka. The results of the study were that the compost fertilizer treatment gave the best results at the plant height of 162.08 cm, the stem diameter was 18.15 mm, the weight of corn was 130.08 grams, the weight of seeds per cob was 236.33 grams, the weight of the cob was 89.00 grams, the biomass weight was 14.27 grams and the production per hectare was 16.88 tons/ha. Compost fertilizer and arbuscular microza treatment gave the highest number of leaves, which was 10.17 sheets. Compost fertilizer treatment provides better results for plant height, stem diameter, fruit weight, seed weight, cob weight, biomass weight and production per hectare and Combination treatment of compost fertilizer, arbuscular mycorrhizae and biosaka does not provide the best results for the growth and production of corn plants planted on saline soil.